The optimal electric energy procurement problem under reliability constraints. (October 2017) - Beraldi, Patrizia; Violi, Antonio; Carrozzino, Gianluca; Bruni, Maria Elena
Abstract: We consider the problem faced by a large consumer that has to define the procurement plan to cover its energy needs. The uncertain nature of the problem, related to the spot price and energy needs, is dealt by the stochastic programming framework. The proposed approach provides the decision maker with a proactive strategy that covers the energy needs with a high reliability level and integrates the Conditional Value at Risk (CVaR) measure to control potential losses. We apply the approach to a real case study and emphasize the effect of the reliability value choice and the difference between risk neutral and adverse positions.